Objective voice analysis for vocal polyps following microlaryngeal phonosurgery - Toran, SiKC; Lal, BK (Kathmandu University Medical Journal, 2010)
Background: Vocal polyps are the products of voice overuse, misuse and abuse as the most common causative factors. Treatment generally advised for them are voice therapy and Microlaryngeal Phonosurgery (MLPS). The improved or changed quality of voice is generally assessed perceptually and can cause intra rater variability. In this study we compared and analysed the acoustic characteristics before and after MLPS. Objective: The purpose of the study was to acoustically determine the changes in voice quality of a group of patients before and after the surgery. Material and methods: The following patients group were studied prior to and in between 3 and 4 weeks of surgery. Altogether there were 23 patients with either unilateral or bilateral vocal polyps. Voice recording and analysis were performed with Dr. Speech acoustic software (Tiger electronics, USA). The parameters analyzed were in terms of perturbation (Jitter and shimmer), harmonic-to-noise ratio (HNR) and fundamental frequency (F0). Results: The results showed that shimmer, HNR and F0 decreased significantly (p<0.05) following MLPS, but jitter though reduced, was not statistically significant (p=0.694). Conclusion: The acoustic output generally improved after MLPS as evidenced by decreased values of all the four acoustic parameters. The study also stress that voice quality can be improved through the phonosurgical procedures. This multidimensional voice analysis can be very helpful in our ability to provide objective clinical analysis of voices with vocal polyps, and following their surgical treatment. Key words: Acoustic analysis; Vocal polyps; Micro-laryngeal phonosurgery DOI: 10.3126/kumj.v8i2.3555 Kathmandu University Medical Journal (2010), Vol. 8, No. 2, Issue 30, 185-189